The Influence of Institutional Voids in the Institutionalization of Bitcoins as a Currency - Sa, Maike Rafael; Verschoore, Jorge Renato; Monticelli, Jefferson Marlon (International Journal of Business, Economics and Management, 2021)
Bitcoin is a social movement, which promises free and decentralized money, absent from the traditional regulatory institutions, but it can be challenging for financial industry regulators and other players in the financial markets. Thus, our study aims to analyze how the institutional voids manifest in the bitcoin institutionalization process as a currency. We adopt the institutional theory, from the perspective of institutional voids, in order to observe the concepts in emerging markets that show the difficulty or the beginning of the institutionalization of bitcoin as a currency. The institutional theory provides an opportunity to understand the reasons for using particular practices, actions, or manifestations. Our method is based on a qualitative exploratory approach with semi-structured interviews to understand how financial market experts perceive this phenomenon. Our results show that it is possible to identify how institutional voids manifest themselves, reinforcing the debate on whether bitcoin is, in fact, a currency.